Perancangan Sistem Informasi Administrasi Ratu Lutanza Wedding Berbasis Java - Hardana, Herdy; Edward, Ruben; Mardiyati, Sri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The Java-based design of the Ratu Lutanza Wedding Administration Information System aims to improve efficiency and quality of service in the Wedding industry. Through the application of the Java programming language, this system design is oriented towards the business needs of Ratu Lutanza Wedding by paying attention to a user-friendly user interface. Grounded Research methods were used in the pilot to gain an in-depth understanding of the user experience, with the results providing valuable insights for system improvement. This design emphasizes good integration with existing administrative processes, as well as the application of an iterative development methodology. Conclusions indicate readiness for continued improvement and continuous development.
Keywords: Information Systems; Design; Marriage Administration; Java